Community Perspectives in Developing Bat-Cave Tourism in Leang Londrong, Bantimurung-Bulusaraung National Park: Comparing The Locals & Tourists - Maulany, Risma Illa; Nurqalbi, Maftukha; Hamzah, Andi Siady; Nasri, Nasri; Asrianny, Asrianny (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
Maros-Pangkep karst formation in South Sulawesi is one of the largest karst environments in the world. One cave located in the area is Leang Londrong and is a part of the management of Bantimurung-Bulusaraung National Park. The Leang Londrong area is known as tourism spot with water-based tourism as the main attraction and it is also known as the main ecosystem service provider in particular as water sources for many areas. This cave is inhabited by some species of bats. Even now the area is designated for water-based tourism, other potential tourism object such bats roosting inside the cave for tourism development has not been explored. Therefore, this study attempts to examine the perception of local community and tourists visiting the area towards nature, cave, bats and its conservation, as well as cave-bats tourism development. The study was conducted between January-April 2022 by distributing questionnaires to 86 respondents consisted of local community, tourists, and government’s representatives. The results indicated that in general the respondents had limited knowledge on nature, cave, bats and its conservation. In particular with bats, the majority of the respondents have not yet been familiar with bats, understood the roles of bats for the environment, and tended to ignore the existence of bats. However, in relation with nature and conservation, bat conservation, and the development of cave and bat tourism in Leang Londrong, all respondents from the tourist’s side agreed to support (>85%) and for the locals, the number was even higher (>90%). Therefore, from the perspectives of local community and tourists, the chance in developing cave and bat tourism in Leang Londrong can be considered possible.